Resource allocation in cognitive radio network with energy harvesting - Yan LONG; Xiaoqian ZHANG; Xuming FANG; Rong HE (Tongxin xuebao)
Considering the diversity of energy harvesting capability and spectrum sensing accuracy of SU,as well as dynamic channel quality,under the constraint of energy causality,the secondary network throughput maximization problem in single-hop cognitive radio networks with energy harvesting was studied.The transmission channel selection,transmission power control and transmission time allocation of SU were jointly optimized.Since the optimization problem was non-convex,by converting it into a series of convex optimization sub-problems,the optimize transmission power and transmission time algorithm (OPTA) was obtained.Compared with the existing resource allocation algorithms,such as,hybrid differential evolution algorithm (HDEA),optimized transmission algorithm (OTA),and random assignment channel algorithm (RA),the simulation results verify the correctness and effectiveness of the proposed algorithm.For example,under the same maximum transmission power constraint,the throughput of the proposed OPTA scheme could increase by around 6%,37% and 50% than that of HDEA,OTA and RA schemes respectively.Under the same channel gain diversity,the throughput of the proposed OPTA scheme could increase by around 30%,60% and 94% than that of HDEA,OTA and RA schemes respectively.Under the same energy harvesting efficiency diversity,the throughput of the proposed OPTA scheme could increase by around 27%,50% and 92% than that of HDEA,OTA and RA schemes respectively.